Management of Cut Throat Injury: A Review of 20 Cases - Parajuli, Ramesh; Limbu, Tilak Raj; Bhandari, Ramesh; Thapa, Suman; Tulachan, Bishow (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Cut throat injury is incised injury or incised resembling injury in the neck usually due to homicidal, suicidal or accidental cause. Multiple vital structures are vulnerable to get injured so it usually requires multi disciplinary approach. The objective of this study is to evaluate cut throat injury in terms of site, severity, cause, motivating factors, age and gender distribution of the victim and the surgical treatment method. MATERIAL AND METHODS: Retrospective study was carried out by reviewing the chart, from May 2010 to April 2014. Demographics of the patients; cause and motivating factors; site, severity and the type of surgical treatment were recorded and analyzed. RESULTS: There were a total of 20 patients, of which 14 were males and 6 were females. The most common age group affected was 20-40 years. Homicide was the commonest cause in 12 (60%) patients, followed by suicidal attempt in 6 (30%) and accidental injury in 2 (10%) patients. Interpersonal conflict and psychiatric illnesses were the most common motivating factors for the homicidal and suicidal cut throat injury respectively. Most of the patients had zone II injury. Primary repair was the most common surgical treatment method. CONCLUSION: Young adults are more vulnerable to cut throat injury with majority having zone II injury and homicide being the most common cause. Primary repair is the most common surgical treatment method. Addressing the root cause of violence and identifying and treating the patients with psychiatric illness with suicidal tendency will probably reduce the incidence of cut throat injury in our society.